The Intertwined Relationship Between Malnutrition and Poverty - Siddiqui, Faareha; Salam, Rehana A.; Lassi, Zohra S.; Das, Jai K. (Frontiers in Public Health, 2020)
Despite social and economic development, the burden of malnutrition across the globe remains unacceptably high. A vital relationship exists between nutritional status, human capital, and economic standing. Malnutrition adversely affects the physiological and mental capacity of individuals; which in turn hampers productivity levels, making them and their respective countries more susceptible to poverty. A two-way link exists between malnutrition and poverty, creating a vicious cycle with each fueling the other. Malnutrition produces conditions of poverty by reducing the economic potential of the population and likewise, poverty reinforces malnutrition by increasing the risk of food insecurity. The aim of the paper is to describe the interconnection between malnutrition and poverty, and to highlight how both serve as the cause and consequence of each other. The paper also discusses ways to move ahead to tackle these issues in a parallel manner rather than in separate silos.